2012
DOI: 10.5501/wjv.v1.i3.79
|View full text |Cite
|
Sign up to set email alerts
|

Selection of RNAi-based inhibitors for anti-HIV gene therapy

Abstract: In the last decade, RNA interference (RNAi) advanced to one of the most widely applied techniques in the biomedical research field and several RNAi therapeutic clinical trials have been launched. We focus on RNAibased inhibitors against the chronic infection with human immunodeficiency virus type 1 (HIV-1). A lentiviral gene therapy is proposed for HIV-infected patients that will protect and reconstitute the vital immune cell pool. The RNAi-based inhibitors that have been developed are short hairpin RNA molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…Here, we selected four anti-HIV-1 shRNA candidates that target essential HIV-1 genes and highly conserved regions of the HIV-1 genome among all HIV-1 subtypes (>73% target conservation of the shRNA target sequence in all virus isolates present in the Los Alamos database), in particular subtype B isolates (>80%). 30 We evaluated the preclinical safety profile in vivo in view of further development of this RNAi-based gene therapy towards clinical trial phase I.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we selected four anti-HIV-1 shRNA candidates that target essential HIV-1 genes and highly conserved regions of the HIV-1 genome among all HIV-1 subtypes (>73% target conservation of the shRNA target sequence in all virus isolates present in the Los Alamos database), in particular subtype B isolates (>80%). 30 We evaluated the preclinical safety profile in vivo in view of further development of this RNAi-based gene therapy towards clinical trial phase I.…”
Section: Discussionmentioning
confidence: 99%
“…A negative impact of a single shRNA on in vitro cell growth and hematopoiesis in the human immune system mouse was observed, which led to its removal from the translational track toward a clinical trial. 22,23 We, therefore, created the combinatorial RNAi vector R3A that expresses the three nontoxic and potent antiviral shRNAs: Pol1, Pol47, and RT5.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, antiviral gene therapy based on the mechanism of RNA interference (RNAi) uses short hairpin RNA (shRNA) inhibitors that target the viral RNA genome 8 , 9 . We previously demonstrated that RNAi attack is influenced by the local RNA structure of the HIV-1 RNA target sequence 10 , 11 and more recently reported that the design of shRNA inhibitors can be significantly improved by the exclusive targeting of accessible HIV-1 RNA domains as determined by SHAPE technology 12 …”
Section: Introductionmentioning
confidence: 99%